1992
DOI: 10.1038/356258a0
|View full text |Cite
|
Sign up to set email alerts
|

A human recombinant haemoglobin designed for use as a blood substitute

Abstract: The need to develop a blood substitute is now urgent because of the increasing concern over blood-transmitted viral and bacterial pathogens. Cell-free haemoglobin solutions and human haemoglobin synthesized in Escherichia coli and Saccharomyces cerevisiae have been investigated as potential oxygen-carrying substitutes for red blood cells. But these haemoglobins cannot be used as a blood substitute because (1) the oxygen affinity in the absence of 2,3-bisphosphoglycerate is too high to allow unloading of enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
201
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(210 citation statements)
references
References 18 publications
3
201
1
5
Order By: Relevance
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars in the erythrocytes (135). Expression of rHb in E. coli and S. cerevisiae was also accomplished with impressive yields (i.e., 2%-10% of the total cellular protein content consists of Hb) (2,28,52,62,74,79,96,97,136,156). Although each system has its own set of advantages and drawbacks, most recent efforts have focused on E. coli production systems.…”
Section: Historical Overview Of Recombinant Hbmentioning
confidence: 99%
See 2 more Smart Citations
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars in the erythrocytes (135). Expression of rHb in E. coli and S. cerevisiae was also accomplished with impressive yields (i.e., 2%-10% of the total cellular protein content consists of Hb) (2,28,52,62,74,79,96,97,136,156). Although each system has its own set of advantages and drawbacks, most recent efforts have focused on E. coli production systems.…”
Section: Historical Overview Of Recombinant Hbmentioning
confidence: 99%
“…Subsequently, Nagai developed a similar system for obtaining unfolded a-globin and reconstituting it with native bchains (92,125,146). Two years later, Somatogen's and Nagai's groups developed an Hb operon for coexpression of a-and bchains with the addition of exogenous heme to produce large amounts of intact, soluble tetrameric Hb in E. coli (62,79,80). Sligar's group developed a similar Hb operon system to express human adult human Hb A (HbA) (57,58).…”
Section: Historical Overview Of Recombinant Hbmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Red cell substitutes: Presently investigations are still in progress on two artificial oxygen transporting fluids-stroma free haemoglobin (SFH) and perflurochemical emulsions (PFC) [22]. Once their clinical use starts, it will be remarkable progress for management of acute haemorrhagic shock.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Scientists at Somatogen, in collaboration with the Medical Research Council of the UK, demonstrated expression in Escherichia coli after the introduction of the human genes into that organism (Hoffman et al, 1990). Somatogen subsequently designed a novel derivative, called`dialpha' haemoglobin that could also be expressed in E. coli (Looker et al, 1992). Dialpha haemoglobin is unique because the two a chains are fused, head-to-tail.…”
Section: Haemoglobin Solutionsmentioning
confidence: 99%